Major vascular complications are reduced by ultrasound guided venous puncture compared to conventional technique in cardiac catheter ablation: a meta-analysis. (3rd October 2022) - Vamosi, P; Kegyes-Brassai, A C; Toth, P; Komlosi, F; Kulyassa, P M; Engh, M A; Fehervari, P; Merkely, B; Geller, L; Nagy, K V
Abstract: Background: Puncture site vascular complications are relatively common during invasive electrophysiology. One of the most promising measures to minimize these adverse events is the use of vascular ultrasound during puncture. Objective: We aimed to carry out a meta-analysis comparing conventional, anatomically guided femoral venous puncture to ultrasound-guided puncture during electrophysiology procedures, which, in contrast to, the previous meta-analyses, used a uniform endpoint and involved novel trials resulting in higher patients numbers. Methods: We conducted a systematic search in relevant electronic databases for articles reporting the rate of vascular complications during EP procedures both with and without ultrasound guidance. We defined major vascular complications (MVCs, as defined in the 2017 HRS/EHRA/ECAS/APHRS/SOLAECE expert consensus) as the primary endpoint. Secondary endpoints were arteriovenous fistula, pseudoanerurysm and major bleeding separately, and minor vascular complications and accidental arterial punctures. Statistical analysis was performed using a random effect model with the Mantel-Haenszel method. Results: A total of 23605 patients were included in the 14 articles matching our selection criteria, and there were data on the primary outcome in 15160 of them (in 11 articles), with 236 (1.6%), who reached the primary endpoint of an MVC. Routine application of ultrasound guidance significantly reduced the incidence of major vascular complications (42/5645 vs. 194/9515, OR 0.36 [0.23–0.55], p<0.001). Furthermore, we found significantly lower incidence in several of our secondary endpoints: for total vascular complications the OR was 0.27 [0.13–0.53] (p<0.001), for major bleedings the OR was 0.42 [0.24–0.74] and for inadvertent artery puncture the OR was 0.24 [0.15–0.38] (p<0.001). Data was insufficiently reported in respect of arteriovenous fistulae and of pseudoanerurysms specifically. Conclusion: With more than double of the number of patients compared to the previous meta-analyses, and with a more consistent MVC definition, we showed that ultrasound guidance for femoral venous puncture has significant benefits, most importantly reduces the incidence of major vascular complications and total vascular complications. Our results underscore the need for a randomized controlled trial in the question, with potentially important implications for daily clinical practice and patient safety. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Project no. NVKP_16-1–2016-0017 ("National Heart Program") has been implemented with the support provided by the Ministry of Innovation and Technology of Hungary from the National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. -Project no. MEC_R-141548 has been implemented with the support provided by the Ministry of Innovation and Technology of Hungary from the National Research, Development and Innovation Fund, financed under the MEC_R_21 funding scheme.